Chiral thiahelicene-based alkyl phosphine-borane complexes: synthesis, x-ray characterization, and theoretical and experimental investigations of optical properties - Dova, Davide; Prager, Stefan; Dreuw, Andreas (The journal of organic chemistry, 2015)
Chiral helical-based phosphanes are challenging and promising ligands, with a great potential for the generation of both organic and organometallic catalysts. We report here the preparation of novel chiral thiahelicene-based alkyl phosphanes, isolated and characterized as air-stable borane adducts, and the investigation of their experimental and theoretical (chir)optical properties. X-ray characterization of a mono- and a disubstituted derivative as a racemic mixture has been performed, which confirms the influence of the number and nature of substituents on the flexibility of the helix. In addition, the absolute configuration inferred from CD spectra of the two enantiomers of a diborane complex has been established from X-ray analysis. State-of-the-art quantum chemical calculations of vibrationally resolved spectra allow, for the first time, for an unambiguous assignment of the experimentally observed peaks in linear absorption and circular dichroism spectra to excited electronic states of this class of thiahelicene phosphorus derivatives.